Method for repairing defects of stone cultural relics through microbial mineralization

By using mineralized liquid prepared by amino acids, sugar alcohol chelated calcium and urea, combined with microorganisms to induce calcium carbonate crystals, the "pan-alkali" problem caused by calcium salt dissolution and crystallization in the repair of stone cultural relics in the prior art was solved, and the strength and weather resistance of the repaired site were improved.

CN119707525APending Publication Date: 2025-03-28NANJING FORESTRY UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411844594.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the prior art repairs the defects of stone cultural relics, the high concentration of calcium salts in the mineralized liquid are prone to dissolve and crystallize, resulting in "alkali-supplementation" of stones, damage to the ornamentality, and accelerates weathering and damage. At the same time, hydraulic lime has low mechanical properties and insufficient durability, which can easily cause bonding and filling effects.

Method used

The mineralized liquid prepared by dissolved in water with amino acids, sugar alcohol chelated calcium and urea is used to induce the formation of a mixture of calcium carbonate crystals and stone chips through microorganisms to repair the defects, avoid excessive calcium salt residues and reduce the problem of salt crystallization.

Benefits of technology

The strength and weather resistance of the repaired parts are improved, and the "scaling" problem caused by calcium salt residue is avoided, and the style consistency and sensory coordination between the repaired parts and the native parts are ensured, and there is no sign of strength deterioration for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707525A_ABST
    Figure CN119707525A_ABST
Patent Text Reader

Abstract

A method for repairing defects of stone cultural relics through microbial mineralization can prevent residual calcium salt from damaging sense organs and strength of the cultural relics, and is characterized by comprising the following steps: a, preparing a mineralized bacteria solution 1; b, dissolving urea and asparaginic acid chelated calcium or urea and sugar alcohol chelated calcium in deionized water to prepare mineralization repair liquid 2; c, filling the defect with an aggregate mixture 4 formed by mixing the mineralized bacteria liquid 1 and the aggregate 3, and then spraying mineralized repair liquid 4 on the filler surface layer; d, the to-be-repaired defect part is sealed, and a grouting opening 5 and a grout outlet 6 are reserved; e, the mineralized bacterium liquid 1 is poured into the defect to be repaired from a grouting opening 5, standing is conducted for 2 h after the defect to be repaired is filled with the mineralized bacterium liquid 1, and then the mineralized repairing liquid 2 is poured twice; and f, the step e is repeated until the mineralized bacteria liquid 1 cannot be injected, residual liquid is evacuated, deionized water is injected to wash the repaired part, then deionized water is injected from a slurry injection opening 5, hydrostatic pressure difference is maintained between the deionized water and a slurry outlet 6, soaking is conducted for 48 h, then soaking liquid is evacuated, and repairing is completed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for repairing stone cultural relics defects by microbial mineralization, belonging to the technical field of cultural relics restoration. Background Art

[0002] Stone cultural relics, especially those exposed to the natural environment, have experienced thousands of years of natural weathering, human destruction, and natural disasters, and often have defects and diseases. These defects often become breakthroughs for water infiltration, acid rain erosion, and freeze-thaw damage. If they are not repaired and managed, the damage to the cultural relics will be further aggravated. Based on the need to protect the common cultural heritage of mankind, it is urgent to carry out the repair of stone cultural relics.

[0003] Existing stone cultural relics are mostly repaired by filling with inorganic materials such as silicate cement, barium oxide, high modulus potassium silicate, or organic polymer materials such as epoxy resin and silicate. Among them, inorganic materials have good anti-aging properties, but poor viscosity and poor compatibility. Silicate cement contains a large amount of silicate, which may also cause "protective damage" to stone cultural relics; while organic polymer materials are toxic and cannot meet the current requirements of green environmental protection, and their weather resistance is questionable.

[0004] Microbial mineralization restoration technology is an emerging cultural relic restoration technology. This technology provides mineralizing bacteria with a mineralizing solution rich in calcium ions and nitrogen sources, and quickly precipitates calcium carbonate crystals with a gelling effect to seal the pores of the stone, cement loose stones, or wrap the surface of the stone to form a protective layer. The calcium carbonate crystals induced by this biological process are non-toxic and harmless, environmentally friendly, have good compatibility and interface strength with the stone, and as an inorganic substance, have relatively good weather resistance. The patent with announcement number CN101270369A proposes to immerse stone cultural relics in a mixed solution containing mineralizing bacteria and calcium chloride or calcium nitrate tetrahydrate, so that a calcium carbonate protective film is formed on its surface to protect the inside of the stone from erosion. The patent with announcement number CN101475401A uses a mixed solution containing mineralizing bacteria, urea and calcium nitrate to undergo a mineralization reaction on the surface of the stone by immersion or coating, generating a continuous, dense and hard calcium carbonate protective layer, thereby protecting and reinforcing the surface of the stone cultural relics. The patent with announcement number CN112125592A proposes to first inject mineralized bacteria liquid into the rock fissures for 4-12 hours, and then inject a cementing liquid containing urea and calcium chloride to repair the rock fissures. The patent with announcement number CN118439837A provides a stone cultural relic fissure grouting method based on the high pH-resistant microbial mineralization process. The method includes grouting repair of small-scale fissures and large-scale fissures. Small-scale fissures are grouted with microbial slurry, which is made by mixing urea, high pH-resistant microbial liquid and hydraulic lime; large-scale fissures are sealed with hot melt adhesive and paper tape before grouting, and grouting is carried out with microbial mortar made of stone powder, hydraulic lime, urea and high pH-resistant microbial liquid, and surface shaping treatment is performed after grouting and curing. Summary of the invention

[0005] Technical issues: There are currently no reports on the use of microbial mineralization technology to repair defects in stone cultural relics. The mineralizing liquid used in the existing microbial mineralization technology to repair stone cracks or to provide stone surface coating protection usually contains high concentrations of calcium chloride or calcium nitrate. When this mineralizing liquid penetrates into stone cultural relics, the calcium salts remaining in it will continue to dissolve and crystallize due to their strong hygroscopicity as the humidity of the environment changes, causing the stone to become "alkaline", which not only greatly affects the ornamental value of the stone cultural relics, but also the crystallization pressure and hydration pressure caused by salt crystallization will also lead to the deterioration of stone strength and accelerate the weathering and damage of stone cultural relics. Hydraulic lime has a low soluble salt content, and using it to repair stone cultural relics can avoid the "salt crystallization" problem, but its mechanical properties are low, its durability is insufficient, and its injectability is poor, which can easily cause unsatisfactory results in the repair process such as bonding and filling. Chelated calcium is a coordination compound with a chelate ring formed by ligands such as amino acids, sugar alcohols, ethylenediaminetetraacetic acid (EDTA) and humic acid and calcium ions. It is mainly used to reduce the deficiency of medium and trace nutrients in crops, improve fertilizer utilization and crop resistance, slow down the decline of soil quality, and improve the soil environment. Among them, the material structure of amino acid and sugar alcohol chelated calcium is similar. Calcium ions are adsorbed on the inside and surface of amino acids or sugar alcohols in the form of white crystals and combined in the form of coordinated covalent bonds. Amino acid and sugar alcohol chelated calcium are dissolved in water together with urea to prepare a mineralization liquid for stone defect repair. It can ionize a small amount of calcium ions and amino acids and sugar alcohols in the mineralization liquid. When mineralizing bacteria decompose urea in the mineralization liquid to continuously produce carbonates, these carbonates meet with free calcium ions to form calcium carbonate precipitation, which gradually consumes calcium ions. The reduction in calcium ion concentration prompts further ionization of chelated calcium, and the ionized calcium ions continue to combine with carbonates to form calcium carbonate, and so on and so forth until the amino acid and sugar alcohol chelated calcium are exhausted. The ionized amino acids and sugar alcohols are easily wrapped and fixed by calcium carbonate because they carry polar groups. Ultimately, the soluble calcium salt content remaining in the repaired part is low, effectively avoiding the adverse effects of salt crystallization problems. Based on this, the present invention provides a method for repairing stone cultural relics defects by microbial mineralization. By optimizing the mineralization liquid formula and matching the corresponding construction process, the repaired part has considerable strength and strong weather resistance, and the residue has low hygroscopicity and is non-toxic and harmless, thereby enriching the ways and methods of stone cultural relics restoration. Technical Solution

[0006] In order to achieve the purpose of the present invention, the present invention discloses a method for repairing the defects of stone cultural relics by microbial mineralization, which is characterized in that the method has the following steps: a. The activated Sporosarcina pasteurii strain was inoculated into a liquid culture medium and cultured at 30°C with shaking for 24 hours to obtain a mineralized bacterial solution 1; b. dissolving 45 to 90 parts of urea and 129 to 256 parts of aspartic acid chelated calcium in 1000 parts of deionized water to prepare a mineralization repair solution 2, or dissolving 45 to 90 parts of urea, 120 to 240 parts of sugar alcohol chelated calcium, 15 to 25 parts of calcium carbonate and 5.6 to 11.2 parts of calcium hydroxide in 1000 parts of deionized water to prepare a mineralization repair solution 2, wherein the sugar alcohol in the sugar alcohol chelated calcium is mannitol or a complex sugar alcohol formed by a mixture of mannitol and erythritol; c. Mix the mineralized bacterial liquid 1 and the aggregate 3 and stir them evenly to form a plastic aggregate mixture 4, then fill the aggregate mixture 4 into the defective part to be repaired, vibrate and compact it and smooth the surface, then spray the mineralized repair liquid 2 evenly on the filler surface layer at intervals of 2 hours, spray it 3 times in total, so that the filler surface layer hardens but does not lose permeability; d. Seal the defective part to be repaired and reserve the grouting port 5 and the grouting outlet 6; e. Pour the mineralized bacterial solution 1 into the defect to be repaired from the grouting port 5, let it stand for 2 hours after saturation, then pour the mineralized repair solution 2, let it stand for 6 hours after saturation, pour the mineralized repair solution 2 again, let it stand for 12 hours after saturation; f. Repeat step e until the mineralized bacterial solution 1 can no longer be poured into the defect to be repaired, then evacuate the residual liquid with negative pressure, inject deionized water from the grouting port 5 to rinse the repaired part, then inject deionized water from the grouting port 5 again and maintain the hydrostatic pressure difference with the slurry outlet 6 to soak for 48 hours, then evacuate the soaking liquid with negative pressure to complete the defect repair;

[0007] The method for repairing stone cultural relics defects by microbial mineralization is characterized in that in step a, each liter of liquid culture medium is prepared by dissolving 10 parts of soy peptone, 10 parts of tryptone, 20 parts of urea, and 5 parts of sodium bicarbonate in 1000 parts of deionized water, and the OD of the mineralized bacterial solution (1) is 600 is 1.8.

[0008] The method for repairing defects of stone cultural relics by microbial mineralization is characterized in that the aggregate 3 in step c is stone chips of the same material as the stone cultural relics to be repaired, with a particle size of 0.075mm to 0.500mm and continuous grading.

[0009] Beneficial effects of the present invention: (1) Using calcium carbonate induced by microorganisms combined with stone chips of the same material to repair defects in stone cultural relics can not only give full play to the advantages of inorganic mineral materials' strong weather resistance, but also overcome the shortcomings of other materials such as poor bonding ability and low repair strength. It can also make the repaired part consistent with the original part in appearance and sensory coordination. (2) Amino acid chelated calcium and sugar alcohol chelated calcium are used for microbial mineralization to repair defects in stone cultural relics. Less soluble calcium salts remain in the repaired part, which will not damage the sensory organs and strength of the cultural relics. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Schematic diagram of microbial mineralization to repair stone cultural relics defects

[0011] Figure numerals: 1-mineralized bacterial liquid; 2-mineralized repair liquid aggregate; 3-aggregate; 4-aggregate mixture; 5-grouting port; 6-slurry outlet. DETAILED DESCRIPTION

[0012] Example 1

[0013] In this case, a method of microbial mineralization to repair defects in stone cultural relics was used to repair the defects of the stone statues of the Shinto Road. The statues were carved from limestone. The defects to be repaired were irregular in shape, with a maximum depth of 51 mm and a volume of 30933 mm. 3 , the method comprises the following steps: a. The activated Sporosarcina pasteurii strain was inoculated into a liquid culture medium and cultured at 30°C for 24 hours to obtain a mineralized bacterial solution 1, wherein each liter of the liquid culture medium was prepared by dissolving 10 parts of soy peptone, 10 parts of tryptone, 20 parts of urea, and 5 parts of sodium bicarbonate in 1000 parts of deionized water. The OD of the mineralized bacterial solution 1 was 600 1.8; b. dissolving 45 parts of urea and 129 parts of aspartate chelated calcium in 1000 parts of deionized water to prepare a mineralization repair solution 2, or dissolving 45 parts of urea, 120 parts of mannitol chelated calcium, 15 parts of calcium carbonate and 5.6 parts of calcium hydroxide in 1000 parts of deionized water to prepare a mineralization repair solution 2; c. Mix the mineralized bacterial liquid 1 and the aggregate 3 and stir them evenly to form a plastic aggregate mixture 4, then fill the aggregate mixture 4 into the defective part to be repaired, vibrate and compact it and smooth the surface, then spray the mineralized repair liquid 2 evenly on the filler surface layer at intervals of 2 hours, spray it 3 times in total, so that the filler surface layer hardens but does not lose permeability, the aggregate 3 is limestone chips, with a particle size of 0.075mm to 0.500mm and continuous grading; d. Seal the defective part to be repaired and reserve the grouting port 5 and the grouting outlet 6; e. Pour the mineralized bacterial solution 1 into the defect to be repaired from the grouting port 5, let it stand for 2 hours after saturation, then pour the mineralized repair solution 2, let it stand for 6 hours after saturation, pour the mineralized repair solution 2 again, let it stand for 12 hours after saturation; f. Repeat step e until the mineralized bacterial solution 1 can no longer be poured into the defect to be repaired, then evacuate the residual liquid with negative pressure, inject 5 times the pore volume of deionized water from the grouting port 5 to rinse the repaired part, then inject 1 times the pore volume of deionized water from the grouting port 5 again and maintain the hydrostatic pressure difference with the slurry outlet 6 for immersion for 48 hours, then evacuate the immersion liquid with negative pressure to complete the defect repair. After the restoration was completed, a colorimeter was used to detect the color difference between the repaired part and the adjacent part, a Barcol hardness tester was used to measure the hardness of the repaired part and the adjacent part, and a conductivity meter was used to measure the conductivity of the immersion solution in step f. The results show that the color difference ΔE is controlled within the perception threshold of 3, and the repaired part is consistent with the original part in style and sensory coordination. The hardness value of the repaired part is between 45 and 52HBa, and that of the original part is 51 to 65HBa. The repaired part has a high strength and meets the requirements of the cultural relics restoration specification that "the strength of the repaired part shall not be higher than that of the original part". The conductivity of the immersion solution is 0.32mS / cm, indicating that the ion content is low and there is little soluble salt residue in the repaired part. A follow-up visit one year later found that there was no alkali efflorescence on the surface of the repaired part, and the hardness value range measured again was still between 45 and 52HBa, and there was no sign of strength deterioration of the stone.

[0014] Example 2

[0015] In this case, a method of microbial mineralization to repair stone cultural relics defects was used to repair white marble railing defects. The defects to be repaired were irregular in shape, with a maximum depth of 37 mm and a volume of 18349 mm. 3 The method comprises the following steps: a. inoculating activated Sporosarcina pasteurii into a liquid culture medium, and culturing the culture medium under shaking at 30°C for 24 hours to obtain a mineralized bacterial solution 1, wherein each liter of the liquid culture medium is prepared by dissolving 10 parts of soy peptone, 10 parts of tryptone, 20 parts of urea, and 5 parts of sodium bicarbonate in 1000 parts of deionized water, and the OD of the mineralized bacterial solution 1 is 600 1.8; b. 60 parts of urea and 172 parts of aspartic acid chelated calcium are dissolved in 1000 parts of deionized water to prepare a mineralization repair solution 2, or 60 parts of urea, 160 parts of mannitol chelated calcium, 20 parts of calcium carbonate and 7.5 parts of calcium hydroxide are dissolved in 1000 parts of deionized water to prepare a mineralization repair solution 2; c. Mix the mineralized bacterial liquid 1 and the aggregate 3 and stir them evenly to form a plastic aggregate mixture 4, then fill the aggregate mixture 4 into the defective part to be repaired, vibrate and compact it and smooth the surface, then spray the mineralized repair liquid 2 evenly on the filler surface layer at intervals of 2 hours, spray it 3 times in total, so that the filler surface layer hardens but does not lose permeability, the aggregate 3 is white marble chips, with a particle size of 0.075mm to 0.500mm and continuous grading; d. Seal the defective part to be repaired and reserve the grouting port 5 and the grouting outlet 6; e. Pour the mineralized bacterial solution 1 into the defect to be repaired from the grouting port 5, let it stand for 2 hours after saturation, then pour the mineralized repair solution 2, let it stand for 6 hours after saturation, pour the mineralized repair solution 2 again, let it stand for 12 hours after saturation; f. Repeat step e until the mineralized bacterial solution 1 can no longer be poured into the defect to be repaired, then evacuate the residual liquid with negative pressure, inject 6 times the pore volume of deionized water from the grouting port 5 to rinse the repaired part, then inject 1 times the pore volume of deionized water from the grouting port 5 again and maintain the hydrostatic pressure difference with the slurry outlet 6 for immersion for 48 hours, then evacuate the immersion liquid with negative pressure to complete the defect repair. After the restoration was completed, a colorimeter was used to detect the color difference between the repaired part and the adjacent part, a Barcol hardness tester was used to measure the hardness of the repaired part and the adjacent part, and a conductivity meter was used to measure the conductivity of the immersion solution in step f. The results show that the color difference ΔE is controlled within the perception threshold of 3, and the repaired part is consistent with the original part in style and sensory coordination. The hardness value of the repaired part is between 55 and 62HBa, and the original part is 72 to 80HBa. The repaired part has a high strength and meets the requirements of the cultural relics restoration specification that "the strength of the repaired part shall not be higher than the strength of the original part". The conductivity of the immersion solution is 0.41mS / cm, indicating that the ion content is low and there is little soluble salt residue in the repaired part. A follow-up visit one year later found that there was no alkali efflorescence on the surface of the repaired part, and the hardness value range measured again was still between 55 and 62HBa, and there was no sign of strength deterioration of the stone.

[0016] Example 3

[0017] In this case, a method of microbial mineralization to repair stone cultural relics defects was used to repair the defects of calcareous sandstone Buddha statues. The defects to be repaired had a regular shape, a depth of 45 mm, and a volume of 102500 mm. 3 The method comprises the following steps: a. inoculating activated Sporosarcina pasteurii into a liquid culture medium, and culturing the culture medium under shaking at 30°C for 24 hours to obtain a mineralized bacterial solution 1, wherein each liter of the liquid culture medium is prepared by dissolving 10 parts of soy peptone, 10 parts of tryptone, 20 parts of urea, and 5 parts of sodium bicarbonate in 1000 parts of deionized water, and the OD of the mineralized bacterial solution 1 is 600 1.8; b. 90 parts of urea and 256 parts of aspartic acid chelated calcium are dissolved in 1000 parts of deionized water to prepare mineralization repair solution 2, or 90 parts of urea, 240 parts of complex sugar alcohol (mannitol and erythritol complex) chelated calcium, 25 parts of calcium carbonate and 11.2 parts of calcium hydroxide are dissolved in 1000 parts of deionized water to prepare mineralization repair solution 2; c. Mix the mineralized bacterial liquid 1 and the aggregate 3 and stir them evenly to form a plastic aggregate mixture 4, then fill the aggregate mixture 4 into the defective part to be repaired, vibrate and compact it and smooth the surface, then spray the mineralized repair liquid 2 evenly on the filler surface layer at intervals of 2 hours, spray it 3 times in total, so that the filler surface layer hardens but does not lose permeability, the aggregate 3 is calcareous sandstone chips, with a particle size of 0.075mm to 0.500mm and continuous grading; d. Seal the defective part to be repaired and reserve the grouting port 5 and the grouting outlet 6; e. Pour the mineralized bacterial solution 1 into the defect to be repaired from the grouting port 5, let it stand for 2 hours after saturation, then pour the mineralized repair solution 2, let it stand for 6 hours after saturation, pour the mineralized repair solution 2 again, let it stand for 12 hours after saturation; f. Repeat step e until the mineralized bacterial solution 1 can no longer be injected into the defect to be repaired, then evacuate the residual liquid with negative pressure, inject 10 times the pore volume of deionized water from the grouting port 5 to rinse the repaired part, then inject 1 times the pore volume of deionized water from the grouting port 5 again and maintain the hydrostatic pressure difference with the slurry outlet 6 for immersion for 48 hours, then evacuate the immersion liquid with negative pressure to complete the defect repair. After the restoration was completed, a colorimeter was used to detect the color difference between the repaired part and the adjacent part, a Barcol hardness tester was used to measure the hardness of the repaired part and the adjacent part, and a conductivity meter was used to measure the conductivity of the immersion solution in step f. The results show that the color difference ΔE is controlled within the perception threshold of 3, and the repaired part is consistent with the original part in style and sensory coordination. The hardness value of the repaired part is between 64 and 71HBa, and the original part is 78 to 89HBa. The repaired part has a high strength and meets the requirements of the cultural relics restoration specification that "the strength of the repaired part shall not be higher than the strength of the original part". The conductivity of the immersion solution is 0.54mS / cm, indicating that the ion content is low and there is little soluble salt residue in the repaired part. A follow-up visit one year later found that there was no alkali efflorescence on the surface of the repaired part, and the hardness value range measured again was still between 64 and 71HBa, and there was no sign of strength deterioration of the stone.

[0018] The implementation methods described above are only illustrative of the basic principles of the present invention, but the implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for repairing defects in stone cultural relics by microbial mineralization, characterized in that The steps of this method are as follows: a. The activated Bacillus pasteurii (Sporosarcina pasteurii) strain was inoculated into a liquid culture medium and cultured at 30°C with shaking for 24 hours to obtain a mineralized bacterial solution (1); b. dissolving 45 to 90 parts of urea and 129 to 256 parts of aspartate chelated calcium in 1000 parts of deionized water to prepare a mineralization repair solution (2); or dissolving 45 to 90 parts of urea, 120 to 240 parts of sugar alcohol chelated calcium, 15 to 25 parts of calcium carbonate and 5.6 to 11.2 parts of calcium hydroxide in 1000 parts of deionized water to prepare a mineralization repair solution (2), wherein the sugar alcohol in the sugar alcohol chelated calcium is mannitol or a complex sugar alcohol formed by a mixture of mannitol and erythritol; c. Mix the mineralized bacterial solution (1) and the aggregate (3) and stir them evenly to form a plastic aggregate mixture (4), then fill the aggregate mixture (4) into the defective part to be repaired, vibrate and compact it and smooth the surface, then spray the mineralized repair solution (2) evenly on the filler surface layer at intervals of 2 hours, spray it 3 times in total, so that the filler surface layer hardens but does not lose permeability; d. Seal the defective part to be repaired and reserve the grouting port (5) and the grouting outlet (6); e. Pour the mineralized bacterial solution (1) into the defect to be repaired from the grouting port (5), let it stand for 2 hours after saturation, then pour the mineralized repair solution (2), let it stand for 6 hours after saturation, pour the mineralized repair solution (2) again, let it stand for 12 hours after saturation; f. Repeat step e until the mineralized bacterial solution (1) can no longer be injected into the defect to be repaired, then evacuate the residual liquid by negative pressure, inject deionized water from the grouting port (5) to rinse the repaired part, then inject deionized water from the grouting port (5) again and maintain a hydrostatic pressure difference with the grouting port (6) to soak for 48 hours, then evacuate the soaking liquid by negative pressure to complete the defect repair.

2. The method for repairing stone cultural relics defects by microbial mineralization according to claim 1, characterized in that In step a, each liter of liquid culture medium is prepared by dissolving 10 parts of soy peptone, 10 parts of tryptone, 20 parts of urea, and 5 parts of sodium bicarbonate in 1000 parts of deionized water. The OD of the mineralized bacterial solution (1) is 60 0 is 1.

8.

3. The method for repairing stone cultural relics defects by microbial mineralization according to claim 1, characterized in that The aggregate (3) in step c is stone chips of the same material as the stone cultural relic to be restored, with a particle size of 0.075 mm to 0.500 mm and continuous grading.

Citation Information

Patent Citations

  • Microorganism cause concrete or concrete, producing method and application thereof

    CN101270369A

  • Preparation method of microbial material for stone cultural relics surface protection

    CN101475401A

  • Microorganism repairing agent for repairing rock cracks and preparation method of microorganism repairing agent

    CN112125592A

  • Stone cultural relic crack grouting method based on high-pH-resistant microorganism mineralization process

    CN118439837A